PELATIHAN GOOGLE APPS BAGI GURU SMK NEGERI 3 PALEMBANG - Ervi Cofriyanti (Politeknik Negeri Sriwijaya, 2018)
The purpose of the community service program is to improve the knowledge and skills of vocational school teachers, especially SMK Negeri 3 Palembang (Public Vocational High School 3 Palembang) about the utilization of information technology, namely the application of Google Apps such as Gmail, Google Drive, Google Doc-Forms and Google Calendar. They can be used to support the learning-teaching dan teacher’s working processes at school. The method of implementing the activity consists of several phases, namely planning phase, implementation phase, observation-evaluation phase and reflection phase. Community service activities are carried out within 6 months. At the beginning and ending of the training, the participants are given a questionnaire (pre-test and post-test) to find out the understanding level of participants. Based on the results of the questionnaire recapitulation on May 30th, 2018, as a result of the reflection of the entire community service activities, 62.5% respondents are answered the knowledge/ technique mastered by the participants after the Google Apps training, 62.5% of the participants answered the instructor’s guidances are quite easy to understand, and as many as 87.5% of participants stated that the training content and method, as well as training design were satisfying.